INOVASI PENGEMASAN PRODUK GULA AREN GUNA MENINGKATKAN NILAI TAMBAH PRODUK DI WILAYAH KESELET AREN DESA TETEBATU SELATAN - Wicaksana, Lalu Tegar; Paorin, Paorin; Fauzi, M. Taufik; Barorot, Kirommin; Ananda, Nadya Azizah Mayla; Ningrum, Amalia Widya; Ernawati, Ernawati; Hasanah, Irma Lailatul; Jalisna, Rohmayani; Maulana, Muhammad Adri; Sobirin, Muhammad (Jurnal Wicara, 2024)
Innovation in packaging for palm sugar products in Tetebatu Selatan Village, Sikur District, East Lombok Regency, aims to enhance local products' added value and competitiveness. This village is known as one of the largest producers of palm sap, which is processed into high-quality palm sugar. However, the current packaging using plastic wrapping makes the product susceptible to damage and moisture. Through community service activities, training and mentoring were provided to palm sugar producers, including techniques for more effective processing and packaging. The outcome of this activity is the development of an attractive and functional pouch package that not only preserves product quality but also increases market appeal. It is hoped that palm sugar products from Tetebatu Selatan Village can compete better in local and national markets and positively impact the local economy.